Almond as Alternative Media for Growth of Staphylococcus aureus and Escherichia coli - Ary Nurmalasari; Leni Marlina; Undang Ruhimat; Rahayu Nirmatul Mutmainah (LPPM STIKes Muhammadiyah Ciamis, 2022)
The high cost of media for microbial culture encourages researchers to create alternative media using local raw materials at low prices. One of the most important media compositions for bacterial growth is protein. This content can be obtained from nuts, one of which is almonds (Prunus dulcis). The purpose of this study is to find natural media that has the potential for the growth of microorganisms at a low price. The research method used is an experimental method to determine the growth of Escherichia coli and Staphylococcus aureus bacteria on natural media of almonds. The results showed the growth of Escherichia coli and Staphylococcus aureus bacteria in this alternative media of almonds. Based on the results of the study, it can be concluded that almond nut media can be applied as an alternative medium in laboratory research, especially in the field of_microbiology. It is suggested that further research should be carried out on natural media which are sources of carbohydrates and proteins as alternative growth media for bacteria.